2023
DOI: 10.1002/adom.202300432
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the Distance Between Donor and Acceptor in Space‐Confined Through‐Space Charge Transfer Emitters for Fast Radiative Decays and High‐Efficiency Organic Light‐Emitting Diodes With Low Efficiency Roll‐Offs

Abstract: Through‐space charge transfer (TSCT) emitters featuring thermally‐activated delayed fluorescence (TADF) are extensively researched but suffer from low radiative decay rates (kr,s) due to insufficient through‐space donor/acceptor interactions. Here, space‐confined TSCT TADF emitters 1–3 with a chemically fixed benzophenone acceptor and a triphenylamine donor on different bridges, that is, 1‐methyl‐9,10‐dihydroanthracene for 1, 4‐methyl‐9H‐xanthene for 2 and 4‐methyl‐9H‐thioxanthene for 3, which exhibit reinforc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Usually, it is necessary to dope TADF materials into host materials to obtain TADF emission. However, the doping method would also lead to intermolecular energy consumption. Therefore, it is essential to design and synthesize TADF materials with high fluorescence efficiency in the solid state. , Since the concept of aggregation-induced emission (AIE) was proposed, it has attracted increasing attention for potential applications in OLEDs and biological imaging, which permits the use of fluorophore solutions at any concentration, thus overcoming the disadvantages of traditional fluorescence emitters. Recently, it has been reported that molecular aggregation and crystal packing modes have a significant influence on TADF properties, ,, and aggregation-induced delayed fluorescence (AIDF) materials can fully combine the advantages of AIE and TADF features, thus contributing to highly efficient emission. …”
Section: Introductionmentioning
confidence: 99%
“…Usually, it is necessary to dope TADF materials into host materials to obtain TADF emission. However, the doping method would also lead to intermolecular energy consumption. Therefore, it is essential to design and synthesize TADF materials with high fluorescence efficiency in the solid state. , Since the concept of aggregation-induced emission (AIE) was proposed, it has attracted increasing attention for potential applications in OLEDs and biological imaging, which permits the use of fluorophore solutions at any concentration, thus overcoming the disadvantages of traditional fluorescence emitters. Recently, it has been reported that molecular aggregation and crystal packing modes have a significant influence on TADF properties, ,, and aggregation-induced delayed fluorescence (AIDF) materials can fully combine the advantages of AIE and TADF features, thus contributing to highly efficient emission. …”
Section: Introductionmentioning
confidence: 99%
“…To rationally construct and modulate the versatile organic D− A systems, various molecular design strategies have been proposed, including the π-conjugated D−A/D−π−A/D−A− D molecular structures, 13 the dynamic D-resonance-A architecture, 14 the multiresonance (MR) structures based on B−N framework etc. with short-range CT, 15 and covalently bonded D−A pairs with through space CT. 16 The key points of these strategies lie in the simultaneous incorporation of multiple functionalities of various D and A fragments with different electronic properties as well as the newly emerged ones by correctly modulating the CT to hybridize the D and A units to a certain level. For organic emitters, the most successful one should be the TADF molecules, 17 where the D unit dominates the highest occupied molecular orbital (HOMO) while the A unit determines the lowest unoccupied molecular orbital (LUMO) with separated frontier orbital distributions for small singlet−triplet splitting energy (ΔE ST ) and facilitated reverse intersystem crossing (RISC) to transform the triplet excitons to singlet ones for delayed fluorescence and thus the theoretically 100% exciton harvest in emission.…”
mentioning
confidence: 99%
“…To rationally construct and modulate the versatile organic D–A systems, various molecular design strategies have been proposed, including the π-conjugated D–A/D−π–A/D–A–D molecular structures, the dynamic D-resonance-A architecture, the multiresonance (MR) structures based on B–N framework etc. with short-range CT, and covalently bonded D–A pairs with through space CT . The key points of these strategies lie in the simultaneous incorporation of multiple functionalities of various D and A fragments with different electronic properties as well as the newly emerged ones by correctly modulating the CT to hybridize the D and A units to a certain level.…”
mentioning
confidence: 99%
“…16−19 However, TSCT-TADF is confronting inevitable challenges nowadays, as there is limited room for exploring new rigid chemical skeletons to support effective cofacial π stacking between D and A subunits. 20,21 In general, steric units are introduced in the adjacent position of D/A to promote the close arrangement of D/A units, so as to enforce the TSCT-TADF process. Although this strategy can effectively improve the luminescence performance, the molecular synthesis becomes complicated and the regulation of molecular spatial structure is still limited.…”
mentioning
confidence: 99%
“…In view of this, a variety of rigid scaffolds have been utilized, e.g., serrated planar carbazole, , fluorene, , and tridimensional triptycene skeletons, affording ideal PLQYs by simultaneously forcing D and A to be tightly stacked and enhancing molecular rigidity to suppress vibration-related nonradiative decay. The past few years have witnessed rapid and prosperous advancements in TSCT-TADF materials and devices based on these excellent rigid bridges. However, TSCT-TADF is confronting inevitable challenges nowadays, as there is limited room for exploring new rigid chemical skeletons to support effective cofacial π stacking between D and A subunits. , In general, steric units are introduced in the adjacent position of D/A to promote the close arrangement of D/A units, so as to enforce the TSCT-TADF process. Although this strategy can effectively improve the luminescence performance, the molecular synthesis becomes complicated and the regulation of molecular spatial structure is still limited. , Intramolecular locking strategy is regarded as an important way to optimize TADF performance .…”
mentioning
confidence: 99%